Hearing Loss in Adult Survivors of Childhood Cancer Treated with Radiotherapy - Amber Khan; Amy Budnick; Dana Barnea; Darren R. Feldman; Kevin C. Oeffinger; Emily S. Tonorezos (MDPI AG, 2018)
The ototoxic effects of radiotherapy have been poorly characterized. We examined adult survivors of childhood cancer who were treated with radiotherapy, which included the head, before the age of 22 years and between 1952 and 2016. Those who received platinum chemotherapy were excluded. Demographic, diagnosis, and treatment outcomes were captured. Audiograms were graded using the Chang and International Society of Paediatric Oncology ototoxicity (SIOP) scales. Among 276 patients with a history of radiation to sites that included the brain, orbit, nasopharynx, and total body irradiation, the median age at treatment was 10.1 years and 59% were male. Of 51 survivors who had post-treatment audiograms, 19 demonstrated severe hearing impairment according to both the Chang and SIOP scales after a median follow-up of 16.6 years. Of those with severe impairment, 10 were using hearing aids. Among the 23 patients with more than one audiogram, five had normal hearing on the first audiogram but hearing loss upon subsequent study. Ototoxic effects of radiotherapy are present in a significant portion of survivors, but impairment may present over time, and our results suggest that many are not being screened. Further, among patients with severe hearing loss, use of hearing aids is not universal. Expansion of access to audiology testing and hearing interventions may be warranted.